Value-Based Education of Religious Moderation for Children in Schools and Families - Fatrica Syafri; Rambat Nursasongko; Muhammad Kristiawan; Wira Hadi Kusuma; Ovi Arieska Meta; Hemaloshinee Vasudevan (The Indonesian Institute of Science and Technology Research, 2025)
This study examines the role of Pendidikan Anak Usia Dini (Early Childhood Education – PAUD) teachers and families in implementing religious moderation-based education in Bengkulu City, as well as to identify the challenges encountered in both school and family environments. The research employed a mixed-methods approach, utilizing interviews and questionnaires distributed to PAUD teachers. The findings reveal that teachers' theoretical understanding of religious moderation remains limited, although some values are indirectly applied in classroom practices. Supporting and inhibiting factors include the family environment, lack of training, and the absence of a specific moderation-based curriculum. This study recommends structured teacher training and strengthened collaboration between schools and families to instill religious moderation values from an early age.